Merdeka Belajar: The Perspective of Progressivism and its Relevance to Teachers as Agents of Change - Kulsum, Umi; Erlitawanty (Jurnal Pendidikan Multikultural Indonesia, 2023)
Merdeka Belajar and Progressivism want changes for the better and with quality. Education practitioners, especially teachers, need to address the change process wisely. This study aims to describe Merdeka Belajar from the point of view of Progressivism in educational renewal—writing method with literature review (literature review). The literature review is carried out by collecting data from various sources of literature as a source of ideas to explore new ideas so that a new theoretical framework can be developed as a basis for solving problems. The results of the writing show that Merdeka Belajar is an effort towards quality education, creating innovative and fun education, and building superior, intelligent, creative human resources to face future challenges; The concept of Merdeka Belajar has parallels with the concept of Progressivism emphasizing independence and freedom for teachers, students, schools towards implementing education in a better direction; Merdeka Belajar in the perspective of Progressivism has relevance to the teacher as an agent of change. Based on these results, the agent of change for teachers implies that teachers are very influential in the renewal of quality education. He was changing himself to act professionally, encouraging students to always progress as a generation that will respond to the challenges of changing times, in line with the goal of Merdeka Belajar in the perspective of Progressivism.